2000
DOI: 10.1016/s0029-7844(00)01015-2
|View full text |Cite
|
Sign up to set email alerts
|

Hand-held computer operating system program for collection of resident experience data1

Abstract: The system of collecting resident encounter data using hand-held computers with the Palm Operating System is easy to use, relatively inexpensive, accurate, and secure. The user-friendly system provides prompt, complete, and accurate data, enhancing the education of residents while facilitating the job of the program director.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…At the graduate level, 13 Obstetrics and Gynecology residents at the Uniformed Services University of Health Sciences and the Walter Reed Army Medical Center piloted the use of a handheld device to track patient encounters 6. These investigators reported that using a PDA to collect resident patient encounter data had a positive impact on the education of the residents and that the handheld computers were “increasingly useful in the daily practice of clinical and academic medicine.” Each of these studies suggests that handheld technologies enhanced medical education; however, they focused on small groups of handheld device users and on one particular kind of application, the patient encounter log (p. 793).…”
mentioning
confidence: 99%
“…At the graduate level, 13 Obstetrics and Gynecology residents at the Uniformed Services University of Health Sciences and the Walter Reed Army Medical Center piloted the use of a handheld device to track patient encounters 6. These investigators reported that using a PDA to collect resident patient encounter data had a positive impact on the education of the residents and that the handheld computers were “increasingly useful in the daily practice of clinical and academic medicine.” Each of these studies suggests that handheld technologies enhanced medical education; however, they focused on small groups of handheld device users and on one particular kind of application, the patient encounter log (p. 793).…”
mentioning
confidence: 99%